2020
DOI: 10.1111/jmwh.13075
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Delayed Umbilical Cord Clamping in Cesarean Birth Using a Novel Method: A Pilot Study of Feasibility and Safety

Abstract: Introduction: Although delayed cord clamping (DCC) is regarded as the standard of care for all vigorous newborns, those born via cesarean birth are less likely to be afforded this option, especially for longer than 30 to 60 seconds. This pilot study was undertaken to determine whether removal of the placenta before cord clamping to allow for DCC of at least 3 minutes during term, uncomplicated cesarean birth is feasible and without apparent safety issues in order to support a large prospective study on the ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Extrauterine Placental Perfusion and Oxygenation in Infants With Very Low Birth Weight from delivery of the infant to placental detachment, data from Welsh et al 12 and our own experience with the EPP procedure showed that times were much shorter than in DCC when staff were experienced with the technique. Second, the procedure does not conflict with the sterility of the operating room.…”
Section: Jama Network Open | Pediatricsmentioning
confidence: 78%
See 1 more Smart Citation
“…Extrauterine Placental Perfusion and Oxygenation in Infants With Very Low Birth Weight from delivery of the infant to placental detachment, data from Welsh et al 12 and our own experience with the EPP procedure showed that times were much shorter than in DCC when staff were experienced with the technique. Second, the procedure does not conflict with the sterility of the operating room.…”
Section: Jama Network Open | Pediatricsmentioning
confidence: 78%
“…This approach, in which infants are born by cesarean delivery with the placenta still connected via an intact umbilical cord and transferred to the resuscitation unit, may work as an alternative approach for PBCC. It was also shown that such an approach for PBCC is safe for mother and infant in babies born at term and provides placental perfusion independently of the mother . Our center has been using this approach in neonatal resuscitation of infants with VLBW born by cesarean delivery for more than a decade and has extended the method by simultaneously applying mask CPAP for respiratory support.…”
Section: Introductionmentioning
confidence: 99%
“…LCC also transports excess red blood cells into the infant, which, combined with the limited ability of the newborn liver to metabolize bilirubin, theoretically makes newborns more susceptible to jaundice. Nevertheless, many researchers have reported no signi cant differences in bilirubin levels and phototherapy rates in infants receiving LCC, compared with neonates receiving ICC [7,9,16,17]. These studies focus on normal pregnant women or those without clear de nitions.…”
Section: Discussionmentioning
confidence: 99%
“…However, some researchers reported that excessive placental blood transport through LCC caused hypervolemia, erythrocytosis, hyperlipemia, and hyperbilirubinemia in neonates, thereby resulting in an elevated likelihood of neonatal jaundice [5][6][7]. But other studies found no effect of LCC on neonatal bilirubin levels and phototherapy rates and there was no signi cant increase in the rate requiring partial exchange transfusion, although it can increase the rate of erythrocytosis [8,9]. Diabetes, caused by impaired glucose metabolism, is one of the most common metabolic disorders, accounting for 3-10% of all pregnancies [10].…”
Section: Introductionmentioning
confidence: 99%
“…Preterm infants show a 50% reduction in the risk of intraventricular haemorrhage, a more than 50% reduction in the need for early red blood cell transfusions, a lower risk of late-onset sepsis, and a 30% reduction in hospital mortality when a DC is performed 39,40,41 . There are even indications that this technique is feasible and safe in Caesarean deliveries and is associated with increased maternal satisfaction and comfort of the medical team in a modern delivery environment 42 . If we add to the documented benefits that, according to the evidence of this study, there is no effect on maternal satisfaction with the experience of labour and birth in full-term pregnancies, the general proposal of adopting DC as a standard of care for the care of labour and birth in mothers with a gestational age between 35 and 42 weeks is reinforced.…”
Section: Discussionmentioning
confidence: 99%